DHA and EPA Prevent Seizure and Depression‐Like Behavior by Inhibiting Ferroptosis and Neuroinflammation via Different Mode‐of‐Actions in a Pentylenetetrazole‐Induced Kindling Model in Mice. Issue 22 (26th September 2022) - Wang, Xueyan; Xiao, Aiai; Yang, Yueqi; Zhao, Yingcai; Wang, Cheng Cheng; Wang, Yuming; Han, Jun; Wang, Zhengping; Wen, Min
Abstract : Scope: It has been reported that eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have anticonvulsant effects, yet the respective mechanism of EPA and DHA on epilepsy is still unclarified. This study aims to investigate the effect of EPA and DHA on pentylenetetrazol (PTZ) induced seizures and depression. Methods and results: The administration of EPA and DHA at a dose of 1% w/w significantly inhibits PTZ‐induced seizures and depressive‐like behavior, whereas EPA outcompetes DHA. Further mechanistic studies reveal that the higher effect of EPA can be partly attributed to the promotion of M2 polarization, inhibition of M1 polarization of microglia, and lower iron content in the brain, resulting from the stronger activation of nuclear factor E2‐related factor 2 (Nrf2). This study finds that DHA and EPA comparably inhibit NLRP3 inflammasome activation but with different mode‐of‐actions: EPA prefers to inhibit the binding of NLRP3 and ASC, while DHA decreases the protein levels of ASC and Caspase‐1. Conclusions: These results indicate that DHA and EPA can efficaciously alleviate PTZ‐induced seizure and depressive‐like behavior but with different efficiency and molecular mechanisms. Abstract : DHA and EPA prevent seizure and depression‐like behavior by inhibiting ferroptosis and neuroinflammation through Nrf2‐HO‐1 pathway in a pentylenetetrazole‐induced kindling model in mice.